Effect of the Rehabilitation Program, ReStOre, on Serum Biomarkers in a Randomized Control Trial of Esophagogastric Cancer Survivors - Kennedy, Susan A.; Annett, Stephanie L.; Dunne, Margaret R.; Boland, Fiona; O’Neill, Linda M.; Guinan, Emer M.; Doyle, Suzanne L.; Foley, Emma K.; Elliott, Jessie A.; Murphy, Conor F.; Bennett, Annemarie E.; Carey, Michelle; et al. (Frontiers in Oncology, 2021)
Background: The Rehabilitation Strategies Following Esophagogastric cancer (ReStOre) randomized control trial demonstrated a significant improvement in cardiorespiratory fitness of esophagogastric cancer survivors. This follow-up study, analyzed the biological effect of exercise intervention on levels of 55 serum proteins, encompassing mediators of angiogenesis, inflammation, and vascular injury, from participants on the ReStOre trial. Methods: Patients > 6 months disease free from esophagogastric cancer were randomized to usual care or the 12-week ReStOre program (exercise training, dietary counselling, and multidisciplinary education). Serum was collected at baseline (T0), post-intervention (T1), and at 3-month follow up (T2). Serum biomarkers were quantified by enzyme-linked immunosorbent assay (ELISA). Results: Thirty-seven patients participated in this study; 17 in the control arm and 20 in the intervention arm. Exercise intervention resulted in significant alterations in the level of expression of serum IP-10 (MD: 38.02 (95% CI: 0.69 to 75.35)), IL-27 (MD: 249.48 (95% CI: 22.43 to 476.53)), and the vascular injury biomarkers, ICAM-1 (MD: 1.05 (95% CI: 1.07 to 1.66)), and VCAM-1 (MD: 1.51 (95% CI: 1.04 to 2.14)) at T1. A significant increase in eotaxin-3 (MD: 2.59 (95% CI: 0.23 to 4.96)), IL-15 (MD: 0.27 (95% CI: 0 to 0.54)) and decrease in bFGF (MD: 1.62 (95% CI: -2.99 to 0.26)) expression was observed between control and intervention cohorts at T2 (p<0.05). Conclusions: Exercise intervention significantly altered the expression of a number of serum biomarkers in disease-free patients who had prior treatment for esophagogastric cancer. Impact: Exercise rehabilitation causes a significant biological effect on serum biomarkers in esophagogastric cancer survivors.